ROLE OF SPIRITUALITY IN RECOVERY AMONG SCHIZOPHRENIA PATIENTS: A SYSTEMATIC REVIEW - Sawab Sawab; Ah Yusuf; Rizky Fitryasari; Hanik Endang Nihayati; Hidayat Arifin; Emi Wuryaningsih (Program Studi Ilmu Keperawatan Universitas Jember, 2025)
Background: Spiritual beliefs in schizophrenia can be both positive, negative. Numerous individuals with schizophrenia engage spirituality as a central coping resource to manage stress, adversity throughout recovery process. Nevertheless, a subset of patients exhibits maladaptive or pathological spiritual beliefs, which may predispose them to employ negative spiritual coping strategies, thereby impeding their overall recovery. Objective: Aimed to explore role of spirituality in recovery from schizophrenia. Methods: Systematic review followed criteria from Centre for Review and Dissemination and Joanna Briggs Institute, as well as PRISMA, to assess quality of included studies. A comprehensive search across 5 databases: Scopus, Web of Science, ProQuest, Science Direct, SpringerLink was conducted to identify relevant articles. A total of 623 articles were screened, with inclusion criteria: studies comprising schizophrenia patients; related to spiritual experiences, descriptions from first-person perspective; journal publications from 2020 to 2025; qualitative or quantitative studies; published in English. 15 articles met inclusion criteria and included in final review. Results: Identified 3 main findings: 1) positive and negative experiences of spirituality in schizophrenia; 2) spiritual coping related to recovery of schizophrenia; 3) relationship between spirituality and recovery of schizophrenia. Conclusion: Spirituality plays a vital role in helping individuals with schizophrenia enhance their self-confidence, self-control, strength,hope, which contributes to their recovery.